A survey on Internet of Things - DOI 10.5752/P.2316-9451.2013v1n2p78 - Agrawal, Shashank; Vieira, Dario (Abakós, 2013)
This paper presents Internet of Things in a wider context. Main enabling factor of this concept is the integration of various technologies. In this paper, we describe the key technologies involved in the implementation of Internet of Things and the major application domain where the Internet of Things will play a vital role. Later we will discuss about the open issues which are to be addressed before the worldwide acceptance of these technologies. There are lots of open issues to address. Here we address the most relevant among them in detail.